Antisemitism and pro-Palestine protests at German universities: Survey results among students and university rectorates - Thomas Hinz; Anna Marczuk; Frank Multrus (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2025)
In Germany, pro-Palestine protests in the form of camps and institute occupations have occurred and continue to take place at universities. Antisemitic incidents have been reported at many of these protests. Following the initial data collection in December 2023, this report provides a new, focused, up-to-date assessment of the opinion climate in the context of the Middle East conflict and antisemitic attitudes at German universities. Exactly one year after the first report, the results of two recent surveys by the Higher Education Research Unit (AG Hochschulforschung) are summarized here. First, based on a large online survey conducted in December 2024 with over 1,800 students, we report on these students' assessments of the conflict and antisemitic tendencies among them. This follows on directly from the previous study mentioned earlier (Hinz et al., 2024), enabling us to describe possible changes compared to last year. In some places, we also examine the assessments and attitudes of students compared to a sample from the general population. Second, we present the results of a simultaneous survey of university rectorates on antisemitic incidents and the universities' reactions to these incidents. At the invitation of the German Rectors' Conference (HRK), a total of 94 university management teams took part in this separate online survey. The results indicate that universities have been strongly affected by antisemitic incidents and that antisemitic resentment remains at a constant level. A high level of vigilance is still required, particularly with regards to Israel-related antisemitism.
urn:nbn:de:bsz:352-2-1dvymsc5qkadm3
Keywords: 320